Exergy, environ–economic and economic analyses of a tubular solar water heater assisted solar still - Bait, Omar (Journal of cleaner production, 2019)
Active solar stills are well known for their higher amount of distillate production than conventional stills. In this paper, a tubular solar collector assisted solar still was suggested for desalting saline water. Its exergy performance, enviro–economic and economic analysis has been carried out. The obtained findings were compared to a simple solar still of similar dimensions. Results revealed that the annual yield of the traditional and modified solar stills was estimated to be ∼405.04 and ∼549.77 kg/m2. The hourly exergy efficiency and global exergy efficiency of the passive system attained ∼7 and ∼30% and similarly for the active system ∼11 and ∼41%, respectively. The economic analysis shows that distilled water cost is minimum when the interest rate and the lifespan are 5% and 30 yrs, respectively, for the simple solar still (i.e. ∼0.018 $/L), while under same conditions, it reaches ∼0.036 $/L in case of improved still. Further, the payback period of the passive and active solar distillers was estimated to be around 7.7 yrs and 21 yrs, respectively, based on the lowest interest rate (5%) and selling price of distilled water of 0.04 $/L. The environmental cost parameter (ZCO2) comes out to be ∼4.42 $/annum on the basis of exergy for the active solar unit. It can be concluded that high distilled water production and less space occupancy are making the enhanced solar unit competitive and feasible. [Display omitted] •Exergy, enviro–economic and economic analysis of a new active solar still.•Exergy performance of the improved solar still is better than a simple solar still.•Annual yield of the modified solar still was estimated to be ∼549.77 kg/m2.•Payback time of the active still is obtained as ∼21 yrs at 0.04 $/L selling price.•Environmental cost, based on exergy was ∼4.42 $/annum in case of improved still.